The Impact of Deforestation on Community Socio-Ecological Resilience: A Review of the Effectiveness of Decentralized Forestry Policies - Novia Angelita Margaretha Silitonga; Andhini Andhini (International Journal of Humanities and Social Sciences Reviews, 2025)
Indonesia, as one of the world’s megabiodiversity countries, possesses vast tropical forests rich in biodiversity and natural resources. Recognizing their ecological and socio-economic importance, the Indonesian government has introduced various forestry policies to preserve forest ecosystems and improve community welfare. One of the key strategies is decentralized forest management, designed to encourage participatory, inclusive, and locally contextual governance. This study adopts a literature review method, drawing from previous research, scientific articles, and relevant policy documents. The objective is to deepen the understanding of deforestation reduction ef-forts, particularly in the context of limited awareness regarding community activities that may harm both social life and environmental sustainability. The primary focus is on assessing the im-pacts of deforestation on socio-ecological resilience, with special attention to the effectiveness of decentralized forestry policies. Findings indicate that deforestation exerts significant and multi-faceted effects on resilience, especially in communities highly dependent on forests for livelihoods and living space. From an ecological perspective, deforestation contributes to biodiversity loss, degradation of ecosystem services, declining soil quality, and weakened ecosystem resilience against environmental change. Such ecological disruptions threaten environmental balance and increase the risks of disasters and natural resource crises, which can have long-lasting implications. Socially, deforestation can undermine local livelihoods, exacerbate poverty, and weaken traditional knowledge systems. These combined effects reduce a community’s capacity to adapt to environ-mental challenges. Therefore, strengthening forestry governance—particularly through decentral-ization and enhanced community participation—is essential to curb deforestation and safeguard socio-ecological sustainability at the local level. Effective implementation requires aligning policy frameworks with local needs, empowering community institutions, and ensuring equitable access to forest benefits.